2017
DOI: 10.3389/fnsys.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

From Anxious to Reckless: A Control Systems Approach Unifies Prefrontal-Limbic Regulation Across the Spectrum of Threat Detection

Abstract: Here we provide an integrative review of basic control circuits, and introduce techniques by which their regulation can be quantitatively measured using human neuroimaging. We illustrate the utility of the control systems approach using four human neuroimaging threat detection studies (N = 226), to which we applied circuit-wide analyses in order to identify the key mechanism underlying individual variation. In so doing, we build upon the canonical prefrontal-limbic control system to integrate circuit-wide infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 74 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…Limitations, strengths, and future directions Some caveats and limitations to these results need to be considered. First, the nature of our analyses indicate that these structures are involved in aversive anticipation but do not provide information about the functional significance of these structures or the dynamic communication between these structures during anxious anticipation (Mujica-Parodi, Carlson, Cha, & Rubin, 2014;Mujica-Parodi, Cha, & Gao, 2017). Additionally, the studies included in the multi-study voxelwise analyses all contained anticipation periods with a one second fixation cue followed by a sixteen second anticipatory countdown.…”
Section: Comparison To Reward Anticipationmentioning
confidence: 94%
“…Limitations, strengths, and future directions Some caveats and limitations to these results need to be considered. First, the nature of our analyses indicate that these structures are involved in aversive anticipation but do not provide information about the functional significance of these structures or the dynamic communication between these structures during anxious anticipation (Mujica-Parodi, Carlson, Cha, & Rubin, 2014;Mujica-Parodi, Cha, & Gao, 2017). Additionally, the studies included in the multi-study voxelwise analyses all contained anticipation periods with a one second fixation cue followed by a sixteen second anticipatory countdown.…”
Section: Comparison To Reward Anticipationmentioning
confidence: 94%
“…If the full spectrum of regulation is represented along an axis designated for each circuit, then-in principle-we can position each psychiatric disorder at precise coordinates within such a phase space. For example, we have shown that the anxious-to-reckless spectrum tracks feedback dynamics within the threat-detection and perceptual circuits (Mujica-Parodi et al, 2017). In contrast, depression likely implicates feedback dynamics with the reward circuit, and complex disorders such as paranoid schizophrenia and addiction are likely to implicate all three circuits and potentially others as well.…”
Section: Computational Psychiatry: Constructing Circuit-based Featurementioning
confidence: 91%
“…Two reasons to suspect that at least some psychiatric disorders implicate allostatic disruption 9 are their vulnerability to perturbation in the form of emotional stress (commonly seen in first-break psychosis and relapse) and trajectories with prominent oscillating features (e.g., bipolar disorder and addiction). Candidate circuits that have been consistently implicated in psychiatrically relevant symptoms include the prefrontal-limbic circuit 10,11 (threat processing, as per anxiety and paranoia), the meso-corticolimbic circuit 12,13 (reward processing, as per anhedonia and addiction), the cortico-thalamic loop 14,15 (sensory processing, as per attentional deficits and hallucinations), and combinations thereof. As evident even from the nomenclature, all three circuits have significant overlap as well as mutual feedback.…”
Section: Mainmentioning
confidence: 99%